What lies in darkness - McDonald, Christina (A Jess Lambert thriller, 2024)
"Late Christmas Eve, the Harper family's car crashed on a desolate stretch outside Black Lake. Sixteen-year-old Alice was found injured by the side of the road--alone. It was as if her parents and younger sister, Ella, had simply disappeared. One year later, Alice is still dealing with nightmares and unanswered questions when she and her friends find Ella's bloodstained backpack in the basement of an abandoned home. As Detective Jess Lambert investigates, she uncovers dark secrets that put her on a collision course with her past. Jess's only witness is haunted by her own ghosts--ghosts that might ultimately be connected to Jess. Jess will do anything to find out what happened to the Harpers--no matter how deep she has to dig. Because neither the living nor the dead are giving up their secrets easily." --